Respuesta :

The answer should be in the form of a(x-h)2 + k.

explanation:

Since we are not translating up or down, the k value is 0. We will not be adding any values to the outputs of the original equation here. a will equal 1 since no stretches are occurring. So we are left with the h value.

f(x) = x2 is given.

g(x) = a horizontal translation of 3 units left. This means that the h value is -3, because in order to move left, you need to take 3 away from all x values (inputs). So the point (2,4) on f(x) would become (-1,4) on g(x).

How do we write this?

g(x) = f(x-h) where h = -3.

So this is g(x) = f(x - (-3)) = f(x+3)

g(x) = (x+3)2

Hope it helps!